2003
DOI: 10.1046/j.1365-8711.2003.06905.x
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf nova oscillations and quasi-periodic oscillations in cataclysmic variables - III. A new kind of dwarf nova oscillation, and further examples of the similarities to X-ray binaries

Abstract: We present measurements of the periods of dwarf nova oscillations (DNOs) and quasi‐periodic oscillations (QPOs) in cataclysmic variable stars (CVs), many culled from published literature, but also others newly observed (in VZ Pyx, CR Boo, OY Car, Z Cha, AQ Eri, TU Men, HX Peg, CN Ori, V893 Sco, WX Hyi and EC2117−54). These provide data for 26 systems. We show that in general PQPO∼ 15 PDNO and that the correlation for CVs extends by three orders of magnitude lower in frequency the similar relationship found for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 79 publications
(119 reference statements)
7
106
0
Order By: Relevance
“…This strongly supports the idea of one and same general mechanism at hand in this accretion disks. The twin peaks ratio around 3:2 for the kHz-QPOs is naturally explained not only for black hole candidates or neutron stars but also for white dwarfs as reported by Warner et al (2003). Indeed, the presence or the absence of a solid surface, a magnetic field or an event horizon play no relevant role in the production of the X-ray variability (Wijnands 2001).…”
Section: Resultsmentioning
confidence: 77%
“…This strongly supports the idea of one and same general mechanism at hand in this accretion disks. The twin peaks ratio around 3:2 for the kHz-QPOs is naturally explained not only for black hole candidates or neutron stars but also for white dwarfs as reported by Warner et al (2003). Indeed, the presence or the absence of a solid surface, a magnetic field or an event horizon play no relevant role in the production of the X-ray variability (Wijnands 2001).…”
Section: Resultsmentioning
confidence: 77%
“…Medium frequencies and the interpretation of peaks in power spectra I will start the discussion concentrating on medium frequencies because this is the range where the most interesting results are observed and where previous studies reported the detection of oscillations (Paper I, Warner et al 2003). Apparently significant signals were also found in the power spectra of other light curves of the present study.…”
Section: Frequency Analysismentioning
confidence: 50%
“…They exhibit a wide range of coherence: Over the course of hours the periods can change by many seconds, but they also may remain stable on the millisecond level. Warner et al (2003) also introduce a second kind of DNOs which they term "longer period DNOs (lpDNOs)" with periods typically 4 times longer than normal DNOs.…”
Section: Frequency Analysismentioning
confidence: 99%
See 2 more Smart Citations